Pengaruh Growth Opportunity, Corporate Social Responsibility, dan Bonus Plan Terhadap Konservatisme Akuntansi - Fardilla Helena Violita; Suwarno, Suwarno (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to test and analyze the influence of growth opportunities, corporate social responsibility, and bonus plans on accounting conservatism. This type of research is quantitative using secondary data. The population used in this research was all manufacturing companies listed on the Indonesia Stock Exchange during the 3 year period 2020-2022, totaling 226 companies, using a purposive sampling technique to produce 175 research samples. This research was tested using SmartPLS 4.0.9.4 using descriptive data analysis, discriminant validity test, coefficient of determination (R2), effect size (F2), path coefficient, and hypothesis testing. The results of the research hypotesis show that (1) growth opportunity has asignificant effect on accounting conservatism, (2) corporate social responsibility has no significant effect on accounting conservatism, and (3) bonus plans have a significant effect on accounting conservatism